Preventive Legal Protection Against Leaks Consumer Data by Company Negligence Financial Technology - Setyawan, Fadjar Ramdhani; Fajrin, Yaris Adhial; Prasetyo, Said Noor; Nuryasinta, Radhityas Kharisma; Alam, Syariful; Kurniawan, Kukuh Dwi; Kurniawan, Wahyudi (KnE Social Sciences, 2024)
Various financial technology companies are currently using standard agreements. Withthe rise of standard agreements, business actors began to include exoneration clausesto release all forms of responsibility for losses suffered by consumers. One of thecompanies that has included the exoneration clause is Koinworks in Article 5 of theKoinworks Terms & Conditions. Based on this statement, the authors conducted thisresearch using two problem formulations, namely what are the legal consequences ofapplying the exoneration clause in standard agreements made by financial technologybusiness actors when viewed from Article 1320 of the Civil Code? And how aboutpreventive legal protection against leakage of consumer data by the negligence offinancial technology companies? To be able to answer the formulation of the problem,the authors use normative juridical research methods with a statutory approach. Theresults of the study show that the legal consequences of applying the exonerationclause in standard agreements made by Financial Technology business actors whenviewed from Article 1320 of the Civil Code, it can be concluded that the exonerationclause can be null and void by law. Then, preventive legal protection needs to becarried out by optimizing supervision by the Financial Services Authority, such astaking action against companies that have violated statutory provisions before theoccurrence of disputes or problems. Keywords: Legal Protection; Data Leakage; Financial Technology Companies